Primary vaginal adenocarcinoma of intestinal type or occult metastatic colon cancer: a diagnostic dilemma from a vaginal skin tag - Russell AL; Haagsma B; Madhuri TK (Dove Medical Press, 2019)
Anna Louise Russell,1 Ben Haagsma,2 Thumuluru Kavitha Madhuri3,4 1Department of Gynae-Oncology, Royal Surrey County Hospital NHS Foundation Trust, Guildford, UK; 2Department of Histopathology, Royal Surrey County Hospital NHS Foundation Trust, Guildford, UK; 3Department of Gynaecological Oncology, Royal Surrey County Hospital NHS Foundation Trust, Guildford, UK; 4Department of Experimental Medicine, Faculty of Health & Medical Sciences, University of Surrey, Guildford, UK Abstract: The presentation of a new vaginal lesion could represent a variety of diagnoses from benign warts to more sinister primary malignancies. Rarely, a new lesion could represent a metastatic deposit from a malignancy elsewhere in the body. Colonic carcinomas are the third most common malignancy, frequently metastasising to the liver and lung. There have been a small number of cases in the literature reporting vaginal metastases from colonic carcinoma and this is usually indicative of advanced disseminated disease. We present an interesting case of a 65-year-old female with a strong family history of bowel cancer who originally presented with a vaginal skin tag that was biopsied and found to be a moderately differentiated adenocarcinoma. The immunohistochemistry profile was cytokeratin (CK) 20 positive/CK 7 negative, highly suggestive of a bowel cancer primary. However, subsequent extensive radiological and endoscopic investigations failed to identify a colonic primary tumor. The vaginal lesion was successfully excised, and no systemic treatments were warranted. To date, no primary cancer has been identified; the patient remains asymptomatic with no clinical signs of disease recurrence 5 years following her initial diagnosis. This case represents a diagnostic dilemma between two very rare diagnoses of either a vaginal metastasis from an occult colonic primary tumor or a primary vaginal adenocarcinoma of endometrioid morphology demonstrating intestinal immunophenotype. Organizing colonic screening is recommended in view of the high risk of colonic adenocarcinoma. Keywords: skin tag, vaginal cancer, metastases, occult malignancy, colon cancer, villiform, intestinal villiform, endometrioid